2004
DOI: 10.1111/j.1525-1594.2004.07320.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Autologous Human Cells for Hard Tissue Regeneration: Preparation and Characterization of Mesenchymal Stem Cells from Bone Marrow

Abstract: Abstract:Mesenchymal stem cells (MSCs) are multipotent cells and can be induced in vitro and in vivo to differentiate not only into the variety of mesodermal cells, but into either ectodermal or endodermal cells. This capability indicates the usefulness of MSCs for tissue engineering. Cell surface antigen analyses using various types of CD antibodies demonstrated that adherent fibroblastic cells derived from fresh human bone marrow are mesenchymal types and the cells showed extensive capability for proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 28 publications
(25 reference statements)
1
109
0
5
Order By: Relevance
“…To differentiate EBs into neuronal cells, retinoic acid (5 M) was treated for 4 days (Okada et al, 2004). Neuronal differentiation of MSCs was performed as described previously (Kotobuki et al, 2004).…”
Section: Embryonic Body Formation and Neuronal Differentiationmentioning
confidence: 99%
“…To differentiate EBs into neuronal cells, retinoic acid (5 M) was treated for 4 days (Okada et al, 2004). Neuronal differentiation of MSCs was performed as described previously (Kotobuki et al, 2004).…”
Section: Embryonic Body Formation and Neuronal Differentiationmentioning
confidence: 99%
“…MSCs derived from her father and a healthy donor were prepared as previously described. 11 In this study, cryopreserved cells were thawed and recultured in basal medium. Cells were used at passage 2 for plasmid transfection and retroviral transduction.…”
Section: Culture Of Mscsmentioning
confidence: 99%
“…10 We have used human MSCs from the patient's bone marrow for treating various diseases centering on bone diseases since 2001. [11][12][13] MSCs and/or osteoblasts differentiated from MSCs have been transplanted into more than 80 patients.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recent studies have demonstrated that MSCs have the ability to aggregate at the site of tissue or organ damage and differentiate into multiple cell types of the mesenchymal lineage, 31,48,56,57 suggesting great potential in their application to gene therapy and the treatment of heart, brain, and necrotic limb disease. 1,10,33 It is the migratory potential of stem cells that allows for their use in therapeutics: Implanted MSCs are able to migrate to the injury site, suggesting that an innate response to the injured microenvironment may produce attractive signals such as cytokines and chemokines to recruit those MSCs. 26,42 The underlying mechanisms that mediate these responses, however, are still unclear in part due to the methodological limitations.…”
Section: Importance Of Stem Cell Migration In Physiology and Medicinementioning
confidence: 99%